Neonatal outcomes according to different therapies for gestational diabetes mellitus - Amanda L. da Silva; Augusto R. do Amaral; Daniela S. de Oliveira; Lisiane Martins; Mariana R. e Silva; Jean Carl Silva (Elsevier, 2017)
Objectives: To compare different neonatal outcomes according to the different types of treatments used in the management of gestational diabetes mellitus. Methods: This was a retrospective cohort study. The study population comprised pregnant women with gestational diabetes treated at a public maternity hospital from July 2010 to August 2014. The study included women aged at least 18 years, with a singleton pregnancy, who met the criteria for gestational diabetes mellitus. Blood glucose levels, fetal abdominal circumference, body mass index and gestational age were considered for treatment decision-making. The evaluated neonatal outcomes were: type of delivery, prematurity, weight in relation to gestational age, Apgar at 1 and 5 min, and need for intensive care unit admission. Results: The sample consisted of 705 pregnant women. The neonatal outcomes were analyzed based on the treatment received. Women treated with metformin were less likely to have children who were small for gestational age (95% CI: 0.09-0.66) and more likely to have a newborn adequate for gestational age (95% CI: 1.12-3.94). Those women treated with insulin had a lower chance of having a preterm child (95% CI: 0.02-0.78). The combined treatment with insulin and metformin resulted in higher chance for a neonate to be born large for gestational age (95% CI: 1.14-11.15) and lower chance to be born preterm (95% CI: 0.01-0.71). The type of treatment did not affect the mode of delivery, Apgar score, and intensive care unit admission. Conclusions: The pediatrician in the delivery room can expect different outcomes for diabetic mothers based on the treatment received. Resumo: Objetivos: Comparar diferentes desfechos neonatais de acordo com as diferentes modalidades de tratamentos do diabetes mellitus gestacional. Métodos: Trata-se de uma coorte retrospectiva. A população do estudo foi composta por gestantes com diabetes gestacional atendidas em uma maternidade pública desde Julho de 2010 a Agosto de 2014. Foram incluídas mulheres com idade mínima de 18 anos, gestação única e com critérios para diabetes mellitus gestacional. Para decisão terapêutica foram considerados glicemias, circunferência abdominal fetal, índice de massa corporal e idade gestacional. Os desfechos neonatais avaliados foram: via de parto, prematuridade, relação do peso com idade gestacional, Apgar no 1° e 5° minuto e necessidade de internação em unidade de terapia intensiva. Resultados: A amostra foi composta por 705 gestantes. Os desfechos neonatais foram analisados com base na terapêutica recebida. Mulheres tratadas com metformina tiveram menor chance de terem filhos pequenos para a idade gestacional (IC 95%: 0,09-0,66) e maior chance de terem um filho adequado para a idade gestacional (IC 95%: 1,12-3,94). A gestante tratada com insulina teve menor chance de ter um filho prematuro (IC 95%: 0,02-0,78). O tratamento feito com a associação de insulina e metformina resultou em maior chance de um recém-nascido grande para a idade gestacional (IC 95%: 1,14-11,15) e menor chance de prematuridade (IC 95%: 0,01-0,71). A modalidade de tratamento não interferiu na via de parto, Apgar e internação em terapia intensiva. Conclusões: O pediatra na sala de parto pode esperar diferentes desfechos para o filho de mãe diabética, com base no tratamento recebido. Keywords: Gestational diabetes mellitus, Therapeutics, Outcomes, Palavras-chave: Diabetes mellitus gestacional, Tratamento, Desfechos